2012
DOI: 10.1007/s00264-012-1537-2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cement injection technique reduces pulmonary embolism in total hip arthroplasty

Abstract: Purpose Cardio-pulmonary damage due to embolism is a feared complication of cemented hip arthroplasty and can be fatal. Embolic events result from an increased intramedullary pressure during cement and stem insertion and can lead to extrusion of bone-marrow elements into the circulation. To reduce embolism and at the same time achieve an ideal cement mantle, the cement injection stem has been designed. In contrast to conventional stems where cement applied before stem insertion (primary cementing technique), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…No significant difference was noted among patients that required bone grafting (p=0.63), internal fixation without fracture reduction (p=0. 43), and open reduction without internal fixation (p=0.087).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…No significant difference was noted among patients that required bone grafting (p=0.63), internal fixation without fracture reduction (p=0. 43), and open reduction without internal fixation (p=0.087).…”
Section: Resultsmentioning
confidence: 96%
“… 42 These patients may have less likely to receive treatment than other patients. Schmidutz et al 43 conducted a randomized trial with 30 patients and observed that secondary cement insertion was able to reduce severe embolic events. With regards to reaming technique, intramedullary reaming has the theoretical higher odds of increasing FES due to the increase in canal pressure and stimulation of an inflammatory response, yet studies have been limited by small sample sizes and this topic requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prophylactic measures such as high-pressure irrigation of the broached femoral channel, distal plugs, venting catheters, distal cortical drill holes, lavage, bone-vacuum suctioning, and secondary cementation have been studied and found to reduce surgical trauma. [113][114][115][116][117][118] Despite these prophylactic measures, installation of hip prostheses without methacrylate cement remains the approach of choice in comorbid patients. [110][111][112] Other prophylactic measures, such as pre-treatment with heparin or a thrombin inhibitor, neutralize most of the coagulation activity and reduce mortality.…”
Section: Prophylaxismentioning
confidence: 99%
“…A pressure of approximately 2000 mmHg (267 kPa) is assumed to be sufficient to obtain an adequate cement mantle [22,23]. Cement applicators that stop automatically at a pressure of 267 kPa were successfully tested (clinically) [24,25]. Based on the earlier studies [22][23][24][25], the increase in intramedullary pressure should stay below 267 kPa while applying the waterjet, which is comparable to the injection pressure during hip stem cementing.…”
Section: Introductionmentioning
confidence: 99%